ANALYSIS OF INSULT AS HUMOR IN THE CONTEXT OF POLITICS THROUGH STAND-UP COMEDY SHOW - Reski Kartini Addas (Journal of Language, Literature and Teaching, 2022)
This research explains the humor styles used in the stand-up comedy show by Kiki Saputri. She owns material that is known as